Psychology as a Biological Science - Biswas-Diener, Robert; Diener, Ed; Open Textbook Library (Open Textbook Library, 2020)
This textbook provides standard introduction to psychology course content with a specific emphasis on biological aspects of psychology. This includes more content related to neuroscience methods, the brain and the nervous system. This book can be modified: feel free to add or remove modules to better suit your specific needs. Please note that the publisher requires you to login to access and download the PDF.
Psychology as Science -- Biological Basis of Behavior -- Sensation and Perception -- Learning and Memory -- Cognition and Language -- Development -- Social -- Personality -- Emotions and Motivation -- Psychological Disorders -- Well-Being
In English.
Description based on online resource
Keywords: Science -- Textbooks; Social sciences -- Textbooks; Biology -- Textbooks; Psychology -- Textbooks